Nail involvement in adult patients with plaque-type psoriasis: prevalence and clinical features - Karen Regina Rosso Schons; André Avelino Costa Beber; Maristela de Oliveira Beck; Odirlei André Monticielo (Sociedade Brasileira de Dermatologia, 2015)
Abstract BACKGROUND: Psoriasis is a disease of worldwide distribution with a prevalence of 1 to 3%. Nail psoriasis is estimated in 50% of patients with psoriasis, and in the presence of joint involvement, it can reach 80%. OBJECTIVE: To study the nail changes - and their clinical implications - presented by patients with psoriasis vulgaris under surveillance in a university hospital from the south of Brazil. METHODS: his cross-sectional study evaluated 65 adult patients from January 2012 to March 2013. Cutaneous severity was assessed according to the Psoriasis Area and Severity Index (PASI). The Nail Psoriasis Severity Index (NAPSI) was used to evaluate patient's nails. The diagnosis of psoriatic arthritis was established according to the Classification Criteria for Psoriatic Arthritis (CASPAR). RESULTS: The prevalence of NP was 46.1%. These patients had a median [interquartilic range (IQR)] NAPSI of 1 (0-15). A total of 63.3% of patients reported aesthetic discomfort or functional impairment related to their nails. Onycholysis was the most common feature (80%). When compared with patients without nail involvement, patients with NP had lower mean age at psoriasis onset [21 (18-41) vs. 43 (30-56) years, p=0,001]; longer disease duration [15.5 (10-24) vs. 6 (2-12) years, p=0.001]; higher PASI [9.2 (5-17) vs. 3.7 (2-10), p=0.044], higher frequency of psoriatic arthritis (43.3 vs. 3.7, p = 0.002) and more often reported family history of psoriasis (40% vs. 7.4%, p = 0.011). CONCLUSION: Onycholysis was the most frequent finding and most patients feel uncomfortable with the psoriatic nail changes that they experience.